Graduate education in qualitative methods in U.S. psychology: current trends and recommendations for the future. Issue 1 (2nd January 2018) - Rubin, Jennifer D.; Bell, Sarah; McClelland, Sara I.
ABSTRACT: The visibility of qualitative research methods (QRM) in U.S. psychology has increased with the dissemination of qualitative research in journals and books, formation of professional and scientific organizations, and recognition in educational institutions. While gains have been made, the current state of doctoral training in qualitative methods remains uncertain. It is unclear what training graduate students receive in U.S. psychology programs about qualitative methodologies and how further gains can be made in expanding visibility of QRM in graduate education. In this mixed-methods study, we surveyed a sample of faculty in U.S. psychology graduate programs about the frequency of QRM course offerings, graduate training, and students' use of QRM in their dissertation research. We also explored qualitative responses from faculty regarding their attitudes about QRM and how these attitudes might help increase or diminish the frequency of methods training available to students. We found that even within graduate programs where there was support for QRM, enduring perceptions about the value of qualitative research limit faculty and graduate students' use of qualitative methodologies in their research. With these findings in mind, we offer several recommendations for increasing the visibility of QRM in U.S. graduate education and the discipline of psychology as a whole.